ANALISIS FAKTOR YANG MEMPENGARUHI PERPINDAHAN MEREK (BRAND SWITCHING) PENGGUNA JARINGAN OPERATOR TRI KE OPERATOR LAIN DI MASA PEMBELAJARAN ONLINE SAAT PANDEMI COVID -19 - Chusnah, Chusnah; Zahratunnisa, Zahratunnisa (Kinerja, 2021)
This researchs purpose to know some factors that influence brand switching Tri operator user to another operator and get result from the pre-survey include the ef ect of product atribute, variety seeking, promotion and price on brand switching. Thisresearch obtained via by questionnaire to 96 respondents which become Tri operator user to students at the As- syafi'iyah Islamic University with population 3.850. Analyst data method that used is regression analysis, correlation, coef icient of determination and hypothesis test. Based on analyst data result, partially product attributes give positive and significant ef ect on brand switching. Variety seeking give positive and significant ef ect on brand switching. Promotion give ositive and significant ef ect on brand switching. Price give positive and significant ef ect on brand switching.